Analysis of Insulin Resistance Levels in Patients with type 1 diabetes - Marjanović, Anja (Medicinski podmladak, 2024)
Introduction: Numerous studies to date have identified the presence of insulin resistance (IR) in type 1 diabetes (T1D), for which the estimated glucose disposal rate (eGDR) is determined. Aim: Analysis of IR levels in patients with T1D and comparison according to the presence of chronic complications of diabetes. Material and methods: The research was done in the form of a retrospective analysis of the database of medical records of 180 patients of both sexes with T1D, disease duration greater than one year in the period 2016-2021, who were divided into two groups based on eGDR levels - IRG (N = 86 , eGDR <8) and ISG (N = 94, eGDR≥ 8). Results: We found that patients with IRG were statistically significantly older (39.35 ± 1.39 vs. 32.13 ± 0.90, p< 0.01), higher BMI (25.93 ± 0.59 vs. 21.78 ± 0.36 kg/ m2, p< 0.01), HbA1c levels (9.63 ± 0.24 vs. 8.30 ± 0.15%, p <0.01) and daily insulin dose (46.51 ± 1.89 vs. 35.89 ± 1.34 j/ day, p< 0.01) compared with ISG patients. At the same time, IRG patients had significantly higher cholesterol levels (4.97 ± 0.14 vs. 4.51 ± 0.10 mmol/ l, p <0.01), LDL (2.97 ± 0.13 vs 2.51 ± 0.09 mmol/ l, p< 0.01) and tgc (1.65 ± 0.16 vs. 1.01 ± 0.06 mmol/ l, p< 0.01) compared to ISG. The IRG has a statistically significantly higher percentage of hypertension (97.27 vs. 2.73%, p< 0.01), retinopathy (25.83 vs. 14.57%, p< 0.01), neuropathy (31.79 vs. 25.16%, p= 0.021) and nephropathy (27.03 vs. 12.16%, p< 0.01) compared with ISG. Conclusion: Patients with T1D and IR were older, with higher BMI, HbA1c, daily insulin doses, with a more atherogenic lipid profile, higher incidence of hypertension, and more frequent microvascular and macrovascular complications. Keywords: T1D, IR, cardiovascular risk, eGDR